Performance Analysis Of The Combination Of Advanced Encryption Standard Cryptography Algorithms With Luc For Text Security - Ady Putra, Wahyu; Suyanto, Suyanto; Zarlis, Muhammad (Politeknik Ganesha Medan, 2023)
Data security is very important as it is easy to exchange data today. Cryptographic techniques are needed as data security techniques. Combining two cryptographic algorithms is a solution for a better level of security. The Advanced Encryption Standard (AES) cryptographic algorithm requires low computational power and is the best symmetric algorithm. The LUC algorithm is an asymmetric algorithm that was developed from the RSA algorithm and has advantages in a better level of security and processing speed. In this research, two symmetric and asymmetric cryptographic algorithms will be combined in a hybrid scheme, namely the AES and LUC algorithms to improve data security. the AES algorithm will encrypt and decrypt messages, while the LUC algorithm performs encryption and decryption of the AES key. The results showed that the combination of the two AES and LUC algorithms was successful. However, the computational time needed by the two algorithms to perform the encryption and decryption process increases. The simulation results of the brute force attack performed show that the LUC algorithm can still be attacked. The greater the value of E (the public key of the LUC algorithm), the longer it takes for the brute force attack to be successful. The value of E is also directly proportional to the computational time required by the LUC. So it can be concluded that the AES algorithm is less precise when combined with the LUC algorithm.